Studies on effects of umbelliferon derivatives against periodontal bacteria; antibiofilm, inhibition of quorum sensing and molecular docking analysis. (July 2020) - Amin, Adnan; Hanif, Muhammad; Abbas, Khizar; Ramzan, Muhammad; Rasheed, Abdur; Zaman, Ali; Pieters, Luc
Abstract: Objective: Umbelliferon derivatives are exclusively found in plants of Ferula spp. that are commonly used in curing various health concerns related to oral cavity. Diabetic patient are especially effected with periodontitis and allied complications. Method: We investigated various compounds isolated from Ferula narthex exudate against clinical strains obtained from diabetic patients with periodontitis. Further antibiofilm, antiquorum sensing and molecular docking studies and ADMET analysis were performed. Results: The docking target included 2Q0J, 2UV0, 3QP5 and 3QP1. HYDE affinity assessment was performed for the first 30 top ranking docked conformations within these active sites. The binding free energy ΔG, FlexX docking score and the most favorable poses for all the compounds were determined. During in vitro analysis, feselol presented high inhibition of Pseudomonas aeruginosa (MIC 0.01 mg/mL, MBC 0.02 mg/mL). Similarly, Feselol presented significant inhibition against clinical strain S. epidermidis (MIC 0.087 mg/mL, MBC 0.174 mg/mL) and S. aureus (MIC 0.087 mg/mL, MBC 0.087 mg/mL) preceded by 10′- R -acetyl-karatavacinol against S. epidermidis (MIC 0.56 mg/mL, MBC 0.56 mg/mL) and S. aureus (MIC 0.28 mg/mL, MBC 0.28 mg/mL). During antibiofilm inhibition assay, 10′ R -acetyl-karatavacinol showed significant inhibition (54% at a final concentration 0.45 mg/mL), whereas slight antiquorum sensing activity was recorded. Conclusions: The umbelliferon derivatives have significant inhibition of clinical isolates and moderate antibiofilm potential. Graphical abstract: Image 1 Highlights: Five Umbelliferone derivatives were tested against 2Q0J, 2UV0, 3QP5 and 3QP1 targets. Structurally related coumarins showed strong hydrogen binding at active sites. Comparative in vitro analysis was performed. Moderate antibiofilm inhibition was recorded.